Interactions between biochar stability and soil organisms: review and research needs. (12th July 2013) - Ameloot, N.; Graber, E. R.; Verheijen, F. G. A.; De Neve, S.
Summary: The stability of biochar in soils is the cornerstone of the burgeoning worldwide interest in the potential of the pyrolysis/biochar platform for carbon (C) sequestration. While biochar is more recalcitrant in soil than the original organic feedstock, an increasing number of studies report greater C‐mineralization in soils amended with biochar than in unamended soils. Soil organisms are believed to play a central role in this process. In this review, the variety of interactions that occur between soil micro‐, meso‐ and macroorganisms and biochar stability are assessed. In addition, different factors reported to influence biochar stability, such as biochar physico‐chemical characteristics, soil type, soil organic carbon (SOC) content and agricultural management practices are evaluated. A meta‐analysis of data in the literature revealed that biochar‐C mineralization rates decreased with increasing pyrolysis temperature, biochar‐C content and time. Enhanced release of CO2 after biochar addition to soil may result from (i) priming of native SOC pools, (ii) biodegradation of biochar components from direct or indirect stimulation of soil organisms by biochar or (iii) abiotic release of biochar‐C (from carbonates or chemi‐sorbed CO2 ). Observed biphasic mineralization rates suggest rapid mineralization of labile biochar compounds by microorganisms, with stable aromatic components decomposed at a slower rate. Comparatively little information is available on the impact of soil fauna on biochar stability in soil, although they may decrease biochar particle size and enhance its dispersion in the soil. Elucidating the impacts of soil fauna directly and indirectly on biochar stability is a top research priority.